Assessment of Young Learners in the Pre-literacy Period in Serbia - Radić Bojanić, Biljana B.; Topalov, Jagoda P. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
Given the fact that English is an obligatory subject in Serbian schools since the first grade, many parents opt for an early start and enroll their children in English classes while they are still in kindergarten, before they can actually read or write. Another context in which young learners learn English in Serbia are the first two grades of primary school, which are also considered to belong to the pre-literacy period because children learn the Latin alphabet only in the second semester of the second grade. For those reasons pupils in Serbia do not read or write in English until the age of 9, so the question is how the teacher can implement assessment in the pre-literacy period. Relying on informal interviews with 15 teachers, this paper intends to investigate how assessment is done with very young learners in the pre-literacy period in private and state-owned primary schools and to present a solution based on the competences that children in this age group already possess, as well as on the teaching and learning aspects which are of great value for the improvement of children’s English language competence.
Keywords: summative assessment; formative assessment; assessment; pre-literacy period; young learners